Sains dalam Sejarah Peradaban Islam - Ziana Farihatul Walida; Muhammad Daffa Handiana; Abdurrahman Syahab; Maftuh Ajmain (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2026)
Islamic civilization reached its peak of scientific glory from the 8th to the 14th century AD, becoming a global intellectual center that produced various discoveries in mathematics, medicine, astronomy, chemistry, physics, and philosophy. This progress did not occur by chance but was driven by theological views that glorified knowledge, supportive political policies, massive translation movements, economic prosperity, practical needs of society, inclusive intellectual traditions, and the integration of revelation, reason, and empirical experience. Prominent figures such as Al-Khwarizmi, Ibn Sina, Ibn al-Haytham, Al-Biruni, Ar-Razi, Al-Zahrawi, Jabir ibn Hayyan, and Ibn Rushd made original contributions that became the foundation for the development of modern science. Islamic civilization also served as a bridge between ancient knowledge and the European Renaissance through the translation of scientific works into Latin. However, decline occurred due to political instability, reduced state support, intellectual stagnation, and external invasions. The legacy of Islamic science remains an important part of the history of global knowledge.